2022
DOI: 10.3389/fmicb.2022.867340
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Piezosphere: The Effects of Decompression on Microbial Growth Dynamics

Abstract: The extent to which the full diversity of the subsurface microbiome can be captured via cultivation is likely hindered by the inevitable loss of cellular viability from decompression during sampling, enrichment, and isolation. Furthermore, the pressure tolerance of previously isolated strains that span surface and subsurface ecosystems can shed light into microbial activity and pressure adaptation in these transition zones. However, assessments of the effects of elevated pressure on the physiology of piezotole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Another critical issue associated with HT-HHP cultivation is the effects of depressurization on the physiology of pressure- incubated microbial cells. Previous studies reported that although depressurization did not kill piezophiles, repeated pressurization and depressurization cycles negatively impacted the growth rate and cell yield of these cells ( Cario et al , 2022 ). This finding highlights the importance of maintaining isobaric conditions throughout the incubation period.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Another critical issue associated with HT-HHP cultivation is the effects of depressurization on the physiology of pressure- incubated microbial cells. Previous studies reported that although depressurization did not kill piezophiles, repeated pressurization and depressurization cycles negatively impacted the growth rate and cell yield of these cells ( Cario et al , 2022 ). This finding highlights the importance of maintaining isobaric conditions throughout the incubation period.…”
Section: Resultsmentioning
confidence: 98%
“…Even when a culture strain is isolated from the deep sea, it is typically cultured and stored at ambient pressure, except for obligate piezophiles. Although previous studies reported the negative effects of depressurization during the HHP cultivation of piezophilic cells ( Cario et al , 2022 ), the effects of an initial change in pressure from the ambient pressure-inoculum to the HHP culture, particularly on the early stages of the growth of piezophiles, remain unclear because of the limited availability of cultivation systems allowing isobaric inoculation. To adapt to the significant increase in pressure, it may be necessary for inoculated piezophiles to undergo physiological changes during the early stages of growth.…”
Section: Resultsmentioning
confidence: 99%
“…This means that, with current systems, a microbial culture must undergo decompression before sampling, which potentially influences the subsequent analyses and results. In addition, faster rates of decompression increase cell damage (Park and Clark, 2002 ; Cario et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, previous studies have adjusted microscope setups to be able to perform high-resolution quantitative imaging of live cells under HHP (Bourges et al, 2020). In addition, the development of microfluidic chip now allows to observe phenotype change of microbes under HHP in real-time, without depressurization (Cario et al, 2022b). Another way to determine potential changes in the membrane lipids upon HHP, might be to determine the microbial genomic potential to synthesize unsaturated and branched-chain fatty acids, which have been seen to increase as a response to HHP.…”
Section: Methodological Challenges Of Studying the Effect Of Hhp On T...mentioning
confidence: 99%